Whole-genome sequence profiling of antibiotic-resistant Staphylococcus aureus isolates from livestock and farm attendants in Ghana. (September 2020) - Egyir, Beverly; Hadjirin, Nazreen F.; Gupta, Srishti; Owusu, Felicia; Agbodzi, Bright; Adogla-Bessa, Tsatsu; Addo, Kennedy Kwasi; Stegger, Marc; Larsen, Anders Rhod; Holmes, Mark A.
Highlights: S . aureus recovered from livestock and farm attendants was characterized by AST and WGS. Isolates were frequently resistant to penicillin (68%) and tetracycline (44%) Twelve (48%) isolates were multidrug resistant (MDR) (>3 classes). 4. ST152-t355, ST9-t1430, and ST133-t8662 were the dominant clones. Typing results provided evidence of a single potential transmission event (t861, PVL-, scn + ). Abstract: Objective: Epidemic methicillin-resistant Staphylococcus aureus (MRSA) clones have been described in Ghana, but so far, no typical livestock-associated MRSA isolates (CC398) have been found. In this study we provide baseline information on antimicrobial resistance, population structure, and virulence gene content of S. aureus isolates from livestock and farm attendants. Methods: Nasal samples were collected from cattle, pigs, goats, sheep, and farm attendants from three farms. Staphylococcus aureus was identified by matrix-assisted laser desorption/ionisation time-of-flight and antimicrobial susceptibility testing was performed using VITEK II (Biomerieux, Marcy l'Etoile, France) and interpreted according to EUCAST guidelines. Whole-genome sequencing was performed using the Illumina, San Diego, CA, USA MiSeq Platform. Results: In total, 401 nasal swab samples were obtained from 57 farm attendants, 208 pigs, 30 goats, 26 sheep, and 80 cattle. The S. aureus isolates ( n = 25) recovered (farm attendants: n = 10; pigs: n = 8; and goats: n = 7) were frequently resistant to penicillin (68%), tetracycline (44%), and ciprofloxacin (32%); two human isolates were MRSA. Twelve isolates (48%) were multidrug resistant (MDR) (>3 classes). Genome sequencing of the isolates revealed ST152-t355, ST9-t1430, and ST133-t8662 as dominant clones among farm attendants, pigs, and goats, respectively. The two MRSA isolates detected belonged to ST8-t334 and ST152-t355. The scn and sak genes associated with human-adaption were detected in 10 isolates; 9 from humans and 1 from a goat. Typing results provided evidence of a single potential transmission event (t861, PVL-, scn +). Conclusion: No MRSA was detected among livestock, perhaps because of low intensive farming; however, the relatively high prevalence of MDR isolates may be a result of inappropriate antibiotic usage in Ghanaian livestock production.